Constituintes químicos de Phyllanthus acuminatus Vahl (Phyllanthaceae): isolamento, caracterização estrutural e atividades biológicas - Duarte, Susyanne de Lima Figueredo (2013)
The genus Phyllanthus belongs to Phyllanthaceae family that consists on non-latescent herbs, shrubs and trees with a predominantly pantropical distribution, including 55 genera and 1,745 species and which was recently detached from the family Euphorbiaceae. In Brazil, the species of the genus Phyllanthus are distributed in subareas of wastelands and backlands in savanna vegetation. The genus is characterized by the presence of several classes of secondary metabolites, including lignans. The objective of this study was to increase knowledge of the genre through the study of Phyllanthus species Phyllanthus acuminatus Vahl, isolating their constituents and evaluating potential activities of these. The following methodologies were used: Column chromatography (CC), analytical thin layer chromatography (CCDA), infrared spectroscopy, Mass, uni and two dimensional 1H and 13C Nuclear Magnetic Resonance, evaluation of modulated antimicrobial activity by efflux pump, antitumor evaluation in vitro and cytotoxicity against erythrocytes. Here we describe the isolation and identification of two lignans, justicidin B, already found in the roots of the species and luclaricin, never previously found in Phyllanthus acuminatus Vahl species. We evaluated the pharmacological activity of justicidin B, major component in the plant s aerial parts, which showed low cytotoxicity against erythrocytes CH50 > 1000 mg / mL, however it showed no biological activity in the modulation test of response towards antimicrobial resistant strains by efflux pump. Regarding antitumor activity it presented activity in several cell lineages, corroborating with literature. Thus this study contributed with new knowledge about the genus and species studied by isolating a new lignan the luclaricin and adds data on the pharmacological activity of justicidin B